PENGARUH PDB, DEFISIT ANGGARAN, CADANGAN DEVISA, SUKU BUNGA LUAR NEGERI TERHADAP UTANG LUAR NEGERI INDONESIA - Marliana, Ni Wayan Selin; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024DO - 10.24843/EEB.2024.v13.i04.p07, 2024)
This study aims to analyze the effect of GDP, budget deficit, foreign exchange reserves, and foreign interest rates simultaneously and partially on Indonesia's foreign debt and to determine the dominant variables affecting Indonesia's foreign debt. This research was conducted in Indonesia with 18 years of observation in the period 2003-2020. The data used is secondary data, the data collection method is non-participant observation. The analytical technique used in this research are descriptive analysis technique and multiple linear analysis. The results of the study found that simultaneously the variables of GDP, budget deficit, foreign exchange reserves, and foreign interest rates had a significant effect on Indonesia's foreign debt. Partially, GDP and foreign exchange reserves have a negative and significant effect, while the budget deficit and foreign interest rates have a positive and significant effect on Indonesia's foreign debt. The budget deficit variable has a dominant effect on Indonesia's foreign debt.